Positive electrode material, positive plate, sodium ion battery and electric equipment
By using sodium iron pyrophosphate crystals to form a core-shell structure in the layered oxide cathode material, the performance degradation caused by expansion during sodium-ion battery cycling is solved, achieving good cycle stability and charge-discharge performance.
Patent Information
- Application Number
- CN202511509836.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-10-22
AI Technical Summary
Existing layered oxide sodium-ion battery cathode materials suffer from expansion problems during cycling due to the large size of sodium ions, which leads to a decrease in cycle performance and affects charge and discharge capacity.
Sodium iron pyrophosphate crystals are used as the outer shell to coat the layered oxide core, forming a core-shell structured cathode material. Some sodium iron pyrophosphate crystals are intercalated into the polycrystalline gaps of the core to suppress lattice distortion and preferentially adsorb sodium ions in the high-voltage region, thereby reducing lattice strain.
It improves the cycle stability and charge/discharge capacity of the cathode material, maintains good ionic conductivity, and exhibits excellent discharge capacity and rate performance, especially at high potentials.
Smart Images

Figure CN120998986A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a positive electrode material, a positive electrode sheet, a sodium-ion battery, and an electrical device thereof. Background Technology
[0002] Layered oxides have become one of the mainstream cathode materials for sodium-ion batteries due to their high capacity and high compaction density. However, because sodium ions have a large ionic radius, they are prone to expansion during adsorption and desorption cycles, leading to a decrease in the cycle performance and lifespan of layered oxides. Therefore, existing technologies have proposed using coating layers to suppress the expansion of layered oxides and improve their cycle performance. However, conventionally used coating layers, such as carbon coating layers, can adversely affect the charge and discharge capacity of layered oxides. Summary of the Invention
[0003] The purpose of this application is to provide a cathode material, cathode sheet, battery and electrical device, wherein the cathode material can maintain its good ionic conductivity and charge / discharge capacity while improving the cycle stability of layered oxide cathode materials.
[0004] One of the purposes of this application is to provide a positive electrode.
[0005] Another objective of this application is to provide a sodium-ion battery.
[0006] One of the purposes of this application is to provide an electrical appliance.
[0007] Firstly, to address the aforementioned problems, this application provides a cathode material, comprising: The core is a secondary particle of layered oxides; The outer shell layer is formed of sodium iron pyrophosphate crystals; the sodium iron pyrophosphate crystals have a size of 2nm~20nm in at least one dimension, and the size of the sodium iron pyrophosphate crystals has a size of 200nm-1μm in at least one dimension.
[0008] Furthermore, in some embodiments of this application, the sodium iron pyrophosphate is partially intercalated into the core.
[0009] Furthermore, in some embodiments of this application, the volume expansion of the positive electrode material after full charge or full discharge or 2000 cycles is no higher than 0.5%.
[0010] Furthermore, in some embodiments of this application, the ionic conductivity of the positive electrode material is not less than 1.0 × 10⁻⁶. -4 S / cm.
[0011] Furthermore, in some embodiments of this application, the sodium iron pyrophosphate crystal is sodium iron pyrophosphate whisker, needle-shaped sodium iron pyrophosphate crystal, or plate-shaped sodium iron pyrophosphate crystal.
[0012] Furthermore, in some embodiments of this application, the sodium iron pyrophosphate phosphate accounts for 1% to 20% of the positive electrode material by mass fraction.
[0013] Furthermore, in some embodiments of this application, the size of the core is 5μm-40μm; the thickness of the outer shell layer is 200nm-1μm.
[0014] Furthermore, in some embodiments of this application, the chemical structural formula of the layered oxide is: Na x Ni y Fe z Mn a M (1-y-z-a) O2; Where x ranges from 0.9 to 1.0; y ranges from 0.1 to 0.5; z ranges from 0.1 to 0.5; and a ranges from 0.1 to 0.5.
[0015] Secondly, this application also provides a positive electrode sheet, comprising the positive electrode material described in the first aspect.
[0016] Thirdly, this application also provides a sodium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator; the separator and the electrolyte are disposed between the positive electrode and the negative electrode. The positive electrode is the positive electrode described in the second aspect.
[0017] Fourthly, this application also provides a battery module, including the sodium-ion battery described in the third aspect or including the positive electrode sheet described in the second aspect or the positive electrode material described in the first aspect.
[0018] This application provides a cathode material, which is a core-shell composite cathode material. Its core is a polycrystalline layered oxide, and its outer shell is a needle-like or sheet-like sodium iron pyrophosphate polyanionic material. During the coating process, the needle-like or sheet-like structures partially intercalate into the intercrystalline gaps of the polycrystalline core, suppressing lattice strain in the layered oxide and improving the cycle stability of the cathode material. Furthermore, after coating with this specific morphology and material of polyanionic material, the cathode material provided in this application not only does not show a decrease in discharge capacity but also exhibits superior discharge capacity, reaching 184 mAh / g or even higher, and its ionic conductivity is also better. Therefore, the cathode material provided in this application not only suppresses the lattice distortion of the O3 phase sodium ion layered oxide but also possesses good charge / discharge capacity and ionic conductivity. In addition, it maintains good capacity retention at high rates, providing cathode material support for the application of sodium-ion fast-charging batteries. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0020] Figure 1 A scanning electron microscope image of the cathode material provided in Embodiment 1 of this application; Figure 2 This is a scanning electron microscope image of the cathode material provided in Embodiment 1 of this application; Figure 3 This is an electron microscope image of the interface of the cathode material provided in Embodiment 1 of this application; Figure 4 This is the XRD pattern of the cathode material provided in Embodiment 1 of this application. Detailed Implementation
[0021] The technical solutions of this application will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0022] In the description of this application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include one or more of the stated features. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0023] The following disclosure provides many different embodiments or examples for implementing different structures of this application. To simplify the disclosure, specific examples of components and arrangements are described below. Of course, these are merely examples and are not intended to limit the scope of this application. Furthermore, reference numerals and / or letters may be repeated in different examples; such repetition is for simplification and clarity and does not in itself indicate a relationship between the various embodiments and / or arrangements discussed. In addition, various specific examples of processes and materials are provided in this application, but those skilled in the art will recognize the application of other processes and / or the use of other materials.
[0024] The poor cycle performance of layered oxides in the O3 phase of sodium-ion cathode materials is primarily attributed to the larger size of sodium ions compared to lithium ions. Sodium ions, during adsorption and desorption, easily cause expansion of the layered oxides, leading to structural damage. Existing technologies primarily employ coating layers to suppress this expansion, thereby improving the stability of the layered oxides during cycling. However, the poor conductivity of the coating material for sodium ions typically affects the charge / discharge capacity of the layered oxides. To address this, the applicant proposes a novel cathode material. This material uses sodium iron pyrophosphate with a specific structure to coat secondary particles of the O3 phase layered oxide. Utilizing the specific structure of the coating, it partially inserts into the crystal interfaces of the secondary particles during coating. This results in a cathode material that not only exhibits good cycle performance but also optimizes charge / discharge capacity and rate performance, overcoming the limitation of existing coating materials that struggle to simultaneously optimize cycle performance, charge / discharge capacity, and rate performance. Specifically, the positive electrode material provided in this application includes: The core is a secondary particle of layered oxides; The outer shell layer is formed of sodium iron pyrophosphate crystals; the sodium iron pyrophosphate crystals have a size of 2nm~20nm in at least one dimension, and the size of the sodium iron pyrophosphate crystals has a size of 200nm-1μm in at least one dimension.
[0025] It should be noted that the "secondary particles" in this application refer to polycrystalline particles, meaning that the core of the cathode material provided in this application is a polycrystalline material of layered oxide, with interfaces between the individual crystals. The outer shell layer is a continuous or discontinuous outer shell layer grown on the surface of the core. It is preferably a continuous outer shell layer. It should be noted that the continuous outer shell layer mentioned in this application means that the sodium iron pyrophosphate crystal particles in the layered structure formed by the outer shell layer material are not distributed in an island-like manner, but rather form a network shell, an interconnected sheet-like shell, or a complete sphere or spheroidal shell. It should be noted that the crystal grain size of the layered oxide in the core of this application is 100nm-1μm, preferably 400nm-500nm.
[0026] The sodium iron pyrophosphate crystal has a size of 2-20 nm in at least one dimension, and the size of the sodium iron pyrophosphate crystal has a size of 200 nm-1 μm in at least one dimension. That is, the sodium iron pyrophosphate crystal in the cathode material provided in this application manifests as sodium iron pyrophosphate whiskers, needle-shaped sodium iron pyrophosphate crystals, or plate-shaped sodium iron pyrophosphate crystals.
[0027] In some embodiments, the sodium iron pyrophosphate crystals in the outer shell layer can also be secondary particles formed by the sequential growth / bonding of primary particles, wherein the particle size in the major axis direction of the sodium iron pyrophosphate single crystal is 50 nm-500 nm, preferably 100-200 nm. The particle size in the minor axis direction of the sodium iron pyrophosphate crystals in the outer shell layer is generally equal to the particle size in the minor axis direction of the single crystal.
[0028] In this application, a needle-like structure refers to a structure in which the length of the crystal is much larger than its width and height, such as a rod-shaped, needle-shaped, or whisker-shaped crystal with an aspect ratio of not less than 10; a plate-like structure refers to a structure in which the thickness of the crystal is much smaller than its length and width, such as a plate-like crystal with a thickness-to-length and width ratio of not less than 8.
[0029] Preferably, the sodium iron pyrophosphate crystals in the cathode material provided in this application are sodium iron pyrophosphate whiskers.
[0030] The cathode material provided in this application not only exhibits excellent cycle performance but also superior charge-discharge capacity and rate performance. This is likely due to the following: the cathode material uses needle-like, plate-like, or whisker-like sodium iron pyrophosphate crystals coated on its surface. When these needle-like, plate-like, or whisker-like sodium iron pyrophosphate crystals grow on the surface of the polycrystalline core, some of these crystals infiltrate between the layered oxide crystals, forming an intercalation structure. This not only suppresses lattice distortion of the O3 phase layered oxide but also forms three-dimensional ion channels embedded in the core. Simultaneously, sodium iron pyrophosphate preferentially adsorbs Na⁺ in the high-voltage region (>3.8V), reducing the lattice strain of the O3 phase, thereby achieving the desired cycle performance of the cathode material, especially in the high-voltage region (>3.8V). This also maintains or even improves its charge-discharge capacity and rate performance. Furthermore, the applicant has found that the charge-discharge capacity of the cathode material provided in this application, especially at high potentials, exhibits performance close to that of the full-potential capacity.
[0031] In some embodiments, the volume expansion of the cathode material after full charge, full discharge, or 2000 cycles is no higher than 0.5%. That is, when the cathode material provided in this application is used in a sodium-ion battery, its volume expansion rate during charging is no higher than 0.5%, its volume change rate during discharging is no higher than 0.5%, and its volume expansion rate after 2000 cycles is no higher than 0.5%. Therefore, the cathode material provided in this application has good stability and excellent cycle stability.
[0032] In some embodiments, the ionic conductivity of the cathode material is not less than 1.0 × 10⁻⁶. -4 S / cm, and can even reach 5.3×10 -4 S / cm.
[0033] In some embodiments, the sodium iron pyrophosphate crystals are needle-like structures with an aspect ratio of 20-30; or The sodium iron pyrophosphate crystals are plate-like structures with a thickness of 2-20 nm; or The sodium iron pyrophosphate crystals have a whisker-like structure with an aspect ratio of 20 to 50.
[0034] In some embodiments, the sodium iron pyrophosphate content in the cathode material is 1% to 20% by mass fraction, preferably 5% to 12%. The proportion of sodium iron pyrophosphate in the cathode material should not be too high or too low. Excessive sodium iron pyrophosphate content leads to excessive shell thickness, resulting in prolonged ion diffusion paths and decreased rate performance. Insufficient sodium iron pyrophosphate content results in insufficient shell coverage, making it difficult to form a relatively continuous shell, thus hindering the suppression of core volume expansion and allowing the electrolyte to directly contact O3, increasing side reactions and decreasing cycle performance.
[0035] In some embodiments, the core has a size of 5μm-40μm; preferably 5μm-15μm. The outer shell has a thickness of 200nm-1μm.
[0036] In some embodiments, the chemical structural formula of the layered oxide is: Na x Ni y Fe z Mn a M (1-y-z-a) O2; Where x ranges from 0.9 to 1.0; y ranges from 0.1 to 0.5; z ranges from 0.1 to 0.5; and a ranges from 0.1 to 0.5.
[0037] In some embodiments, the chemical structural formula of the sodium iron pyrophosphate is: Na4Fe3(PO4)2(P2O7).
[0038] To enable those skilled in the art to better implement this solution, this application also provides a method for preparing this cathode material, including the following steps: (1) Preparation of layered oxide precursors Sodium, iron, nickel, manganese and dopants are provided in a molar ratio of 1:0.4:0.3:0.2:0.1. The core raw materials are mixed with the first solution and dispersion, and the Zeta potential is adjusted to above +35mV by adding the dispersion. The mixture is then ground and spray-dried to obtain layered oxide precursor particles. (2) Preparation of sodium iron pyrophosphate precursor The outer shell material is provided in a molar ratio of sodium source, iron source and phosphorus source of 4:3:4. The outer shell material and the second solution are stirred in a water bath at 40~90℃ for 4~24h to obtain a transparent sol-like sodium iron pyrophosphate precursor. (3) The sodium iron pyrophosphate precursor and the layered oxide precursor particles are mixed at a mass ratio of 1:10~50 and ultrasonically dispersed for 30~180 min. The mixture is then concentrated at 50~80℃ until the sodium iron pyrophosphate precursor increases in weight by 5-8%, so that the sodium iron pyrophosphate precursor is uniformly attached to the surface of the layered oxide precursor particles to obtain the composite material. (4) Sintering The composite material is vacuum dried for 4-24 hours, heated to 400-450°C in an environment of (91.5-95%) protective gas and (5%-8.5%) oxygen, and sintered at this temperature for 4-12 hours. The sintering atmosphere is then adjusted to a second sintering atmosphere, and sintered at 600-900°C for 4-12 hours, followed by annealing at 200-300°C for 2-8 hours to obtain the cathode material of this application.
[0039] In step (1), the sodium source can be at least one of sodium carbonate, sodium hydroxide, and sodium dihydrogen phosphate. The iron source in step (1) can be at least one of ferric nitrate, ferric oxide, ferric phosphate, ferrous sulfate, ferrous oxalate dihydrate, and elemental iron. The nickel source in step (1) can be at least one of nickel hydroxide, nickel nitrate, and nickel sulfate. The manganese source in step (1) can be at least one of manganese oxide, manganese trioxide, manganese hydroxide, and manganese sulfate. The dopant in step (1) can be at least one of copper, vanadium, titanium, and aluminum. The first solution can be at least one of deionized water, ethylene glycol, N-methylpyrrolidone, and ethanol. The dispersion can be at least one of polyacrylic acid, ethylene glycol, and polyvinyl alcohol.
[0040] In step (2), the sodium source can be at least one of sodium carbonate, sodium hydroxide, and sodium dihydrogen phosphate. In step (1), the iron source can be at least one of ferric nitrate, ferric oxide, ferric phosphate, ferrous sulfate, ferrous oxalate dihydrate, and elemental iron. The second solution can be at least one of deionized water, ethylene glycol, N-methylpyrrolidone, and ethanol.
[0041] Preferably, the sodium source in step (1) can be the same as that in step (2) to reduce the introduction of more impurities.
[0042] The second sintering atmosphere is a protective gas such as nitrogen, argon, or helium, or a mixture of protective gas and carbon dioxide or water vapor. Preferably, it is a mixture of protective gas and carbon dioxide or water vapor; more preferably, the carbon dioxide in the second sintering atmosphere accounts for 3.2%-5.5% by mass, and the gaseous water in the second sintering atmosphere accounts for 1.0%-2.2 wt% by mass.
[0043] Secondly, this application also provides a positive electrode sheet, comprising the positive electrode material described in the first aspect.
[0044] Thirdly, this application also provides a sodium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator; the separator and the electrolyte are disposed between the positive electrode and the negative electrode; the positive electrode is the positive electrode described in the second aspect.
[0045] The electrolyte can be a liquid electrolyte, a solid electrolyte, or other electrolytes. The separator can be a polyolefin separator or a polyolefin separator with a ceramic coating. The negative electrode sheet can include a current collector and a coating applied to the surface of the current collector. The current collector may include a metal foil, such as aluminum foil or copper foil. The coating may include a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent. The negative electrode active material may be a carbon material or other material capable of sodium ion insertion / extraction. Similarly, the positive electrode sheet may also include a current collector and a coating applied to the surface of the current collector. The coating may include the aforementioned positive electrode material and a binder.
[0046] Fourthly, this application also provides a battery device, including the sodium-ion battery described in the third aspect or including the positive electrode sheet described in the second aspect or the positive electrode material described in the first aspect.
[0047] The electrical device provided in this application includes a battery module composed of multiple batteries, used to provide power to the device. Exemplary examples of the electrical device include mobile communication devices (e.g., mobile phones), computers (e.g., laptops, iPads, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0048] To facilitate a better understanding of the innovative aspects of this application by those skilled in the art, the technical solutions of this application are further described in detail below with reference to embodiments. The embodiments of this application described in detail below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0049] Example 1 This embodiment provides a cathode material, and the preparation method of the cathode material is as follows: (1) Preparation of layered oxide precursors Sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, and copper oxide were provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.4:0.3:0.2:0.1. These components, along with an ethanol solution, were added to a planetary ball mill. Ammonium polyacrylate dispersant was added, and the Zeta potential was adjusted to above +40mV. The mill was then ground at 400 rpm for 24 hours to obtain wet abrasive. The wet abrasive was then spray-dried under the following conditions: inlet air temperature: 220-250℃; outlet air temperature: 80-100℃; atomization pressure: 0.3-0.5MPa; nozzle diameter: 0.5mm; and feed rate controlled by a peristaltic pump: 10mL / min. This yielded spherical layered oxide precursors with an average particle size D50 of 8μm.
[0050] (2) Preparation of sodium iron pyrophosphate precursor Ferrous oxalate dihydrate and sodium pyrophosphate were dissolved in 0.1 mol / L citric acid solution at a molar ratio of 3:1 and stirred in a water bath at 80°C for 4 hours to form a blue-green transparent sol, thus obtaining a nano-micelle-like precursor of sodium iron pyrophosphate. (3) Add the sodium iron pyrophosphate precursor to a transparent sol at a mass ratio of 1:10, disperse ultrasonically for 30 minutes, and concentrate under reduced pressure at 50°C until the sol completely coats the particle surface (weight gain of 5-8%); so that the sodium iron pyrophosphate precursor is uniformly attached to the surface of the layered oxide precursor particles to obtain the composite material. (4) Sintering The composite material was vacuum dried at 100℃ for 12 hours; then heated to 400℃ and sintered in an atmosphere of 95% N2 + 5% O2 for 4 hours. N2 was then introduced to adjust the sintering atmosphere to nitrogen, and the temperature was raised to 600℃ for 6 hours, followed by annealing at 300℃ for 2 hours to obtain the cathode material of this application: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 11Na4Fe3(PO4)2(P2O7), as Figures 1-4 As shown.
[0051] Example 2 This embodiment provides a cathode material, and the preparation method of the cathode material is as follows: (1) Preparation of layered oxide precursors Sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, and copper oxide were provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.3:0.3:0.3:0.1. These components, along with an ethanol solution, were added to a planetary ball mill. Ammonium polyacrylate dispersant was added, and the Zeta potential was adjusted to above +40mV. The mill was then ground at 400 rpm for 24 hours to obtain wet abrasive. The wet abrasive was then spray-dried under the following conditions: inlet air temperature: 220-250℃; outlet air temperature: 80-100℃; atomization pressure: 0.3-0.5MPa; nozzle diameter: 0.5mm; and feed rate controlled by a peristaltic pump: 10mL / min. This yielded spherical layered oxide precursors with an average particle size D50 of 13μm.
[0052] (2) Preparation of sodium iron pyrophosphate precursor Ferrous oxalate dihydrate and sodium pyrophosphate were dissolved in 0.1 mol / L citric acid solution at a molar ratio of 3:1 and stirred in a water bath at 80°C for 4 hours to form a blue-green transparent sol, thus obtaining a nano-micelle-like sodium ferric pyrophosphate precursor. (3) Add the sodium iron pyrophosphate precursor to a transparent sol at a mass ratio of 1:10, disperse ultrasonically for 30 minutes, and concentrate under reduced pressure at 50°C until the sol completely coats the particle surface (weight gain of 5-8%); so that the sodium iron pyrophosphate precursor is uniformly attached to the surface of the layered oxide precursor particles to obtain the composite material. (4) Sintering The composite material was vacuum dried at 100℃ for 12 hours; then heated to 400℃ and sintered in an atmosphere of 95% N2 + 5% O2 for 4 hours. N2 was then introduced to adjust the sintering atmosphere to nitrogen, and the temperature was raised to 750℃ for 6 hours, followed by annealing at 300℃ for 2 hours to obtain the cathode material of this application: NaNi. 0.3 Fe 0.3 Mn 0.3 Cu 0.1 O2@1 / 11Na4Fe3(PO4)2(P2O7). Example 3 This embodiment provides a cathode material, and the preparation method of the cathode material is as follows: (1) Preparation of layered oxide precursors Sodium carbonate, ferric phosphate, nickel oxide, manganese trioxide, and copper oxide were provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.4:0.3:0.2:0.1. The sodium carbonate, ferric phosphate, nickel oxide, manganese trioxide, copper oxide, and ethanol solution were added to a planetary ball mill, along with ammonium polyacrylate dispersant. The Zeta potential was adjusted to above +40mV, and the milling speed was 400 rpm for 24 hours to obtain wet abrasive. The wet abrasive was then spray-dried under the following conditions: inlet air temperature: 220-250℃, outlet air temperature: 80-100℃, atomization pressure: 0.3-0.5MPa, nozzle diameter: 0.5mm, and peristaltic pump-controlled feed rate: 10mL / min, to obtain spherical layered oxide precursors with an average particle size D50 of 12μm.
[0053] (2) Preparation of sodium iron pyrophosphate precursor Sodium carbonate and ferric phosphate were dissolved in 0.1 mol / L citric acid solution at a molar ratio of 1:1.2 and stirred in a water bath at 80°C for 4 hours to form a blue-green transparent sol, thus obtaining a nano-micelle-like precursor of sodium iron pyrophosphate. (3) Add the sodium iron pyrophosphate precursor to a transparent sol at a mass ratio of 1:10, disperse ultrasonically for 30 minutes, and concentrate under reduced pressure at 50°C until the sol completely coats the particle surface (weight gain of 5-8%); so that the sodium iron pyrophosphate precursor is uniformly attached to the surface of the layered oxide precursor particles to obtain the composite material. (4) Sintering The composite material was vacuum dried at 100℃ for 12 hours; then heated to 400℃ and sintered in an atmosphere of 95% N2 + 5% O2 for 4 hours. Next, N2 + 4% CO2 + 2% H2O was introduced to adjust the sintering atmosphere to a mixture of protective gas and 4% carbon dioxide and 2% water vapor. The temperature was then raised to 600℃ for 6 hours, followed by annealing at 300℃ for 2 hours, yielding the cathode material of this application: NaNi. 0.3 Fe 0.3 Mn 0.3 Cu 0.1 O2@1 / 11Na4Fe3(PO4)2(P2O7).
[0054] Example 4 Compared to Example 1, in this embodiment, the mixing mass ratio of the layered oxide precursor particles and the sodium iron pyrophosphate precursor is adjusted to 1:8. The remaining steps are the same as in Example 1, yielding the cathode material: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 9Na4Fe3(PO4)2(P2O7).
[0055] Example 5 Compared to Example 1, in this embodiment, the mixing mass ratio of the layered oxide precursor particles and the sodium iron pyrophosphate precursor is adjusted to 1:20. The remaining steps are the same as in Example 1, yielding the cathode material: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 20Na4Fe3(PO4)2(P2O7).
[0056] Comparative Example 1 (1) Preparation of layered oxide precursors Provide 1 mole of sodium source, 0.3 mole of iron source, 0.4 mole of nickel source, 0.2 mole of manganese source and 0.1 mole of copper source, the sodium source, iron source, nickel source, manganese source and copper source are the same as in the example, and the remaining steps are the same as step (1) in Example 1, to obtain layered oxide precursor particles. (2) Preparation of Na iron phosphate precursor Provides 1 mole of sodium source, 1 mole of Fe source, 1 mole of phosphorus source, and process gel. (3) The sodium iron phosphate precursor and the layered oxide precursor are mixed in a mass ratio of 1:10 and ultrasonically dispersed for 30 minutes to make the sodium iron phosphate precursor uniformly adhere to the surface of the layered oxide precursor particles, thereby obtaining the composite material. (4) Sintering The composite material was vacuum dried at 100°C for 12 hours; then heated to 400°C and sintered for 4 hours; then heated to 600°C and sintered for 6 hours; and finally annealed at 300°C for 2 hours. The sintering atmosphere was the same as in Example 1, resulting in the cathode material of this application: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 11Na Ferric Phosphate.
[0057] Comparative Example 2 Compared to Example 1, this comparative example involves vacuum drying the composite material at 100°C for 12 hours during the sintering step; then heating to 300°C for 4 hours, followed by sintering at 550°C for 6 hours, and annealing at 200°C for 2 hours. The sintering atmosphere is the same as in Example 1, and the remaining steps are the same as in Example 1, yielding the following cathode material: NaNi 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 10Na4Fe3(PO4)2(P2O7).
[0058] Comparative Example 3, compared to Example 1, involved vacuum drying the composite material at 100°C for 12 hours during the sintering process; then heating to 300°C and sintering for 4 hours, followed by heating to 500°C and sintering for 6 hours, and finally annealing at 200°C for 2 hours. The sintering atmosphere was the same as in Example 1, and the remaining steps were the same as in Example 1, yielding the cathode material: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 10Na4Fe3(PO4)2(P2O7).
[0059] Comparative Example 4 Compared to Example 1, in step (3) of this comparative example, 1g of the sodium iron pyrophosphate precursor and 100g of layered oxide precursor particles are mixed at a mass ratio of 1:100. The other steps are the same as in Example 1, resulting in the positive electrode material: NaNi 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 101Na4Fe3(PO4)2(P2O7).
[0060] Comparative Example 5 Compared to Example 1, in step (3) of this comparative example, 1g of the sodium iron pyrophosphate precursor and 5g of layered oxide precursor particles are mixed at a mass ratio of 1:20. The other steps are the same as in Example 1, resulting in the following cathode material: NaNi 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2@1 / 21Na4Fe3(PO4)2(P2O7).
[0061] Comparative Example 6 (1) Preparation of layered oxide precursors Sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, and copper oxide are provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.4:0.3:0.2:0.1. The sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, copper oxide, and ethanol solution are added to a planetary ball mill. The remaining steps are the same as step (1) in Example 1. (2) The layered oxide precursor and glucose are mixed and ground at a mass ratio of 1:10; the glucose is uniformly attached to the surface of the layered oxide precursor particles to obtain the composite material. (3) Sintering The composite material was vacuum dried at 100°C for 12 hours; then heated to 400°C and sintered for 4 hours, then heated to 600°C and sintered for 6 hours, and finally annealed at 300°C for 2 hours. The sintering atmosphere was the same as in Example 1, resulting in the cathode material of this application: NaNi. 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2 / C Comparative Example 7 (1) Preparation of layered oxide precursors Sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, and copper oxide were provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.4:0.3:0.2:0.1. These components, along with an ethanol solution, were added to a planetary ball mill. Ammonium polyacrylate dispersant was added, and the Zeta potential was adjusted to above +40mV. The mill was then ground at 400 rpm for 24 hours to obtain wet abrasive. The wet abrasive was then spray-dried under the following conditions: inlet air temperature: 220-250℃; outlet air temperature: 80-100℃; atomization pressure: 0.3-0.5MPa; nozzle diameter: 0.5mm; and feed rate controlled by a peristaltic pump: 10mL / min. This yielded spherical layered oxide precursors with an average particle size D50 of 8μm.
[0062] (2) Sintering The spherical sodium iron pyrophosphate precursor was vacuum dried at 100°C for 12 hours; then heated to 400°C and sintered for 4 hours, then heated to 600°C and sintered for 6 hours, and annealed at 300°C for 2 hours, wherein the sintering atmosphere was the same as in Example 1, to obtain O3 layered oxide.
[0063] (3) Ferrous oxalate dihydrate and sodium pyrophosphate were dissolved in 0.1 mol / L citric acid solution at a molar ratio of 3:1 and stirred in a water bath at 80°C for 4 hours to form a blue-green transparent sol, thus obtaining a nano-micelle sodium pyrophosphate precursor. The sodium pyrophosphate precursor was concentrated and dried, then sintered at 400°C for 4 hours, then heated to 600°C for 6 hours, and annealed at 300°C for 2 hours. The sintering atmosphere was the same as in Example 1, thus obtaining sodium pyrophosphate.
[0064] (4) The layered oxide of O3 obtained in steps (3) and (4) and sodium iron pyrophosphate are mixed at a mass ratio of 1:10 and sintered at 400°C in a nitrogen atmosphere for 6 hours to form a composite cathode material of sodium iron pyrophosphate coated with O3.
[0065] Comparative Example 8 (1) Preparation of layered oxide precursors Sodium carbonate, ferrous oxalate dihydrate, nickel hydroxide, manganese trioxide, and copper oxide were provided in a molar ratio of Na:Ni:Fe:Mn:Cu = 1:0.4:0.3:0.2:0.1. These components, along with an ethanol solution, were added to a planetary ball mill. Ammonium polyacrylate dispersant was added, and the Zeta potential was adjusted to above +40mV. The mill was then ground at 400 rpm for 24 hours to obtain wet abrasive. The wet abrasive was then spray-dried under the following conditions: inlet air temperature: 220-250℃; outlet air temperature: 80-100℃; atomization pressure: 0.3-0.5MPa; nozzle diameter: 0.5mm; and feed rate controlled by a peristaltic pump: 10mL / min. This yielded spherical layered oxide precursors with an average particle size D50 of 8μm.
[0066] (2) Sintering The spherical sodium iron pyrophosphate precursor was vacuum dried at 100°C for 12 hours; then heated to 400°C and sintered for 4 hours, then heated to 600°C and sintered for 6 hours, and finally annealed at 300°C for 2 hours, with the sintering atmosphere being the same as in Example 1, to obtain O3 layered oxide: NaNi 0.4 Fe 0.3 Mn 0.2 Cu 0.1 O2.
[0067] To verify the superior performance of the cathode material provided in this application, the applicant used the cathode materials obtained in Examples 1-5 and Comparative Examples 1-8 as cathode active materials to prepare corresponding sodium-ion batteries, and the specific preparation is as follows: (1) Preparation of positive electrode sheet: The positive electrode material, conductive carbon black, polyvinylidene fluoride and carbon nanotubes are mixed and stirred in a mass ratio of 95:1:3:1. N-methylpyrrolidone solvent is added to adjust the slurry to a positive electrode slurry with a solid content of 60% and a viscosity of 6000 mPa·s. The negative electrode slurry is transferred and coated onto a 15 μm thick carbon-coated aluminum foil using the transfer coating method. The coated electrode sheet is rolled to a compaction density of 3 mg / cm3. The rolled electrode sheet is die-cut into electrode sheets with a length of 48 mm and a width of 38 mm for later use.
[0068] (2) Preparation of negative electrode sheet: Hard carbon material, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber were mixed and stirred in a mass ratio of 95:1:3:1. N-methylpyrrolidone solvent was added to adjust the slurry to a negative electrode slurry with a solid content of 60% and a viscosity of 6000 mPa·s. The negative electrode slurry was transferred and coated onto a 15 μm thick carbon-coated aluminum foil using a transfer coating method. The coated electrode sheet was then rolled to a thickness of 3 mg / cm. 2 The compaction density is determined; the rolled electrode sheets are then die-cut into electrode sheets with a length of 48mm and a width of 38mm for later use.
[0069] (3) Fabrication of sodium-ion batteries: The slit positive and negative electrode sheets are stacked on a stacking machine. The separator is made of PP / PE / PP three-layer material to form a soft-pack cell. Electrolyte (components: carbonate solvent and 1M sodium hexafluorophosphate) is injected, packaged, dried, and subjected to capacity testing to obtain a sodium-ion battery.
[0070] The sodium-ion batteries prepared above were subjected to morphology characterization tests, cycle performance tests, charge-discharge capacity tests, and rate performance tests; the specific test methods are as follows. (1) Cyclic performance test Using the Xinwei testing machine, the battery cells were cyclically tested at a 1C / 1C rate, with a voltage range of 2.5V-4.2V.
[0071] (2) Charge and discharge capacity test Using the Xinwei testing machine, the battery cell was charged at 0.5C and discharged at 1C. The 1C discharge capacity was taken as the standard capacity, and the voltage range was 2.5V-4.2V.
[0072] (3) Ratio performance test Using the Xinwei testing machine, the battery cells were tested at 1C / 1C, 1C / 2C, 1C / 5C, and 1C / 10C rates, with a voltage range of 2.5V-4.2V.
[0073] The test results are shown in Table 1.
[0074] from Figures 1-3 It can be seen that the morphology of the coating layer on the surface of the cathode material provided in this application is a whisker-like structure, and some of the whiskers are embedded in the core. Thus, the cathode material provided in this application has a core-shell structure, and the crystal structure of its outer shell layer is a whisker structure.
[0075] Table 1
[0076] As shown in Table 1, the sodium-ion battery based on the cathode material provided in this application exhibits excellent charge-discharge capacity and good cycle performance. Furthermore, its capacity retention rate is very high at this rate, reaching over 94% at 5C and even exceeding 89% at 10C. This demonstrates the superior performance of the cathode material provided in this application for fast-charging applications. In addition, its ionic conductivity is also high. Compared to Example 4, Comparative Example 4 used less coating material. Although its charge-discharge capacity was also high, its cycle performance decreased significantly, and its capacity retention rate dropped rapidly at high rates, with lower ionic conductivity. In Comparative Example 5, when excessive sodium iron pyrophosphate was used for coating, its ionic conductivity decreased instead of increasing, and its cycle performance and capacity retention rate at high rates also declined.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A positive electrode material, characterized in that, include: The core is a secondary particle of layered oxides; The outer shell layer is formed of sodium iron pyrophosphate crystals; the sodium iron pyrophosphate crystals have a size of 2~20nm in at least one dimension; and the sodium iron pyrophosphate crystals have a size of 200nm-1μm in at least one dimension.
2. The cathode material according to claim 1, characterized in that, The sodium iron pyrophosphate is partially intercalated into the core.
3. The cathode material according to claim 1, characterized in that, The volume expansion of the cathode material after full charge, full discharge, or 2000 cycles is no higher than 0.5%.
4. The cathode material according to claim 1, characterized in that, The ionic conductivity of the positive electrode material is not less than 1.0 × 10⁻⁶. -4 S / cm.
5. The positive electrode material according to claim 1, characterized in that, The sodium ferric pyrophosphate crystals are sodium ferric pyrophosphate whiskers, needle-shaped sodium ferric pyrophosphate crystals, or plate-shaped sodium ferric pyrophosphate crystals.
6. The cathode material according to claim 1, characterized in that, The sodium iron pyrophosphate phosphate accounts for 1% to 20% of the total content of the cathode material by mass fraction.
7. The cathode material according to claim 1, characterized in that, The core has a size of 5μm-40μm; the outer shell has a thickness of 200nm-1μm.
8. The positive electrode material according to claim 1, characterized in that, The chemical structural formula of the layered oxide is: Na x Ni y Fe z Mn a M (1-y-z-a) O2; Where x ranges from 0.9 to 1.0; y ranges from 0.1 to 0.5; z ranges from 0.1 to 0.5; and a ranges from 0.1 to 0.
5.
9. A positive electrode plate, characterized in that, Includes the cathode material as described in any one of claims 1 to 8.
10. A sodium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a separator; the separator and the electrolyte are disposed between the positive electrode and the negative electrode. The positive electrode is the positive electrode as described in claim 9.
11. A battery module, characterized in that, It includes the sodium-ion battery of claim 10, or the positive electrode sheet of claim 9, or the positive electrode material of any one of claims 1 to 8.
Citation Information
Patent Citations
Positive electrode material composition, preparation method thereof, positive electrode plate and sodium ion battery
CN119008896A
Doped and coated composite sodium battery positive electrode material as well as preparation method and application thereof
CN119725455A
Positive electrode material and preparation method therefor, positive electrode, sodium battery and electric device
WO2025091897A1